Edaphic recovery of degraded soils with combined use of leucaena (Leucaena leucocephala) and vetiver grass (Chrysopogon zizanioides) in Vandúzi, Mozambique - Tomás, Domingos; Cristóvão, Luís; João, Gila Abilio; Dauala, Gonçalves Albino; Mulima, Eduardo Pinto; Rocha, Alessandro (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
Soil recovery is a process aimed at reversing its degradability by incorporating favorable conditions (physical, chemical, and biological) to restructure life so that, through intervention, it can regenerate. This study aimed to analyze the potential combined use of leucaena (Leucaena leucocephala) and vetiver grass (Chrysopogon zizanioides) for the recovery of degraded soils in the Nhamurenguera area, Vandúzi District, Mozambique. The experimental method included soil study (physical-chemical analyses), area preparation (field and seedbed), field management, topographic survey, and qualitative and quantitative visual assessment of the developing seedlings. A total of 650 leucaena and 680 vetiver grass seedlings were planted in an area of 0.5 ha, with a spacing of 4 m between rows and 2 m between seedlings of both species in consort. Three months after planting, the survival and adaptability levels of the seedlings were evaluated. The results showed that 17% of the leucaena individuals and 12% of the vetiver grass died due to ant attacks and insufficient moisture, despite the use of mulching. Regarding the seedlings’ reaction to soil conditions, 94% of leucaena and 79% of vetiver showed slow development in the first 3 months of planting due to soil compaction and low nutrient availability (leaching). After four years, soil chemical parameters were evaluated and compared with pre-leucaena/vetiver consortium soil data. The pH values, electrical conductivity, NPK contents, calcium, and magnesium increased, improving soil quality and indicating a soil recovery process to prepare it for subsequent agricultural use, especially for cereal and legume crops.